Analysis of land tillage practices and related problems among rice farmers in the tropic of sub-saharan Africa (Journal of the Bangladesh Agricultural University, 2018)
The decision “to till” or “not to till” is premised on the farmers’ perception of the inherent negative effects of tilling vis-à-vis the crop output performance and the profitability of the farm venture. Land tillage practices and land related problems of farmers were assessed in Agricultural Zone I of Niger State, Nigeria. Furthermore, the relation between land related problems and rice production levels was also investigated. Cross sectional data was collected for the analysis using questionnaire from one hundred and twenty (120) rice farmers. Descriptive statistics as well as the Chi-Square Test were used to analyze data collected. Findings revealed that 40.8 % and 56.7% of the respondents utilize manual and mechanized tillage methods on their farms, respectively. Thus indicating a majority (97.5%) of the farmers intensively tilling the soil as a cultivation practice. Land related problems reported by farmers include induce errosion, loss of nutrient, insect pest attack and change in soil texture. Furthermore, it was also found that farmers operating at a higher level of production experience more land related problems on the fields. The Chi square analysis revealed a strong relationship between tillage method and prevalence of land related problems and incidences of pests and diseases. Also levels of production at which farmers operate was found to have a relationship with the incidence of tillage related problems observed on the farms. It is therefore the opinion of this study that agronomist need to research and put forward environmentally friendly tillage methods that best suits farmer needs in the study area. Furthermore, farmer education about the negative effects of tilling without recourse to the environment is also advocated.J. Bangladesh Agril. Univ. 16(1): 98-103, April 2018